The effect of NAMA Foundation’s interventions on student engagement in co-curricular and out-of-school activities in Indonesia, Kyrgyzstan, and Tanzania - Kassim, Siti Kholijah; Ssekamanya, Siraje Abdallah; Syed Mahmood, Syarifah Rohaniah; Mansor, Norwati (NAMA Foundation, 2025)
This study examines the effect of the NAMA Foundation’s interventions on engagement in co-curricular and out-of-school activities, a key component of holistic student development, in secondary schools across Indonesia, Kyrgyzstan, and Tanzania. Employing a longitudinal mixed-methods approach, baseline (2021) and mid-term (2022) data were collected using student questionnaires covering domains such as participation in sports, clubs, teamwork, and community activities. Independent t-tests were conducted to compare pre- and post-intervention means for each country, while effect sizes were calculated using Cohen’s d. Results revealed statistically significant improvements (p < 0.05) in overall student participation and engagement in extracurricular and out-of-school activities, with most items showing medium to large effect sizes (Cohen’s d > 0.5 to > 0.8) in Indonesia and Kyrgyzstan, and small to moderate effects in Tanzania. These findings affirm the substantial impact of structured, inclusive programs on fostering holistic development, in line with prior research. Nevertheless, the study highlights ongoing challenges related to resource allocation and equitable access, especially in Tanzania. The results underscore the importance of continued investment in extracurricular infrastructure and policy reforms to promote holistic growth in diverse educational settings.